2011
DOI: 10.1111/j.1468-3148.2011.00624.x
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Life Events, Social Support and Psychological Problems in Adults with Intellectual Disabilities

Abstract: Background Several studies have reported relationships between life events and psychological problems in people with intellectual disabilities. In contrast to the general literature, data have consistently been collected via proxy informants and putative moderator variables such as social support have not been examined. Materials and Methods Thirty-eight adults with intellectual disabilities completed three psychological measures in a semi-structured interview setting: the Bangor Life Events Schedule for Intel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 56 publications
2
41
0
1
Order By: Relevance
“…Consent was obtained following a capacity assessment protocol akin to that of previous researchers, whereby an information sheet was read to participants with questions asked throughout to assess their comprehension of the study and their rights as a participant. Demographic data were collected, and an initial interview was conducted with the patient and their caregivers (where appropriate), allowing familiarization with the interviewer, establishing treatment time frames and factual information for subsequent interviews.…”
Section: Methodsmentioning
confidence: 99%
“…Consent was obtained following a capacity assessment protocol akin to that of previous researchers, whereby an information sheet was read to participants with questions asked throughout to assess their comprehension of the study and their rights as a participant. Demographic data were collected, and an initial interview was conducted with the patient and their caregivers (where appropriate), allowing familiarization with the interviewer, establishing treatment time frames and factual information for subsequent interviews.…”
Section: Methodsmentioning
confidence: 99%
“…Results of several studies (Lunsky & Bramston ; Hubert‐Williams et al . ; Balboni et al . ) indicated that self‐reports and the reports of others are both necessary for objective views of the experiences of people with intellectual disability.…”
Section: Discussionmentioning
confidence: 99%
“…Support staff rate clients' CB based on overt behaviours. Results of several studies (Lunsky & Bramston 2006;Hubert-Williams et al 2011;Balboni et al 2013) indicated that self-reports and the reports of others are both necessary for objective views of the experiences of people with intellectual disability. It is important to remain including both assessment strategies, that is self-report and report by proxies, in future research.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the Bangor Life Events Schedule for Intellectual Disabilities (BLESID) 63 self-report version was used to record participants' recent life events. This questionnaire was used to record the important life events that had taken place in participants' lives over the previous 12 months and the impact that these events had on their lives.…”
Section: Life Eventsmentioning
confidence: 99%